This is Yesterday : Just what is it that makes the Consortium's collection so different, so appealing? - Bourriaud, Nicolas; Calvo Poyato, Carmen; Chacón Álvarez, José Antonio; Douroux, Xavier; Gautherot, Franck; Grenier, Catherine; López Moreno, Maria Luisa; Centre Pompidou, Paris; Le Consortium, Dijon (Sevilla : CAAC (Centro Andaluz de Arte Contemporaneo), 1999)
Boltanski, Christian ; McCaslin, Matthew ; Rutault, Claude ; Zaugg, Rémy ; Knifer, Julie ; Morellet, François ; Lavier, Bertrand ; Parreno, Philippe ; Buren, Daniel ; Diao, David ; Geoffroy, Christiane ; Kawara, On ; McCollum, Allan ; Parrino, Steven ; Uglow, Alan ; Fleury, Sylvie ; Gillick, Liam ; Cattelan, Maurizio ; Genzken, Isa ; Knoebel, Imi ; Rondinone, Ugo ; Ruthenbeck, Reiner ; Stockholder, Jessica ; Toroni, Niele ; Wallace & Donohue ; Bulloch, Angela ; Burkhard, Balthasar ; Armleder, John ; Benedetto, Steve Di ; Mosset, Olivier ; Scott, Michael ; Dejanov, Plamen ; Heger, Swetlana ; Feldmann, Hans-Peter ; Lawler, Louise ; Graham, Dan ; Jones, Sarah ; Marioni, Tom ; Morris, Sarrah ; Noland, Cady ; Tiravanija, Rirkrit ; Cavellini, Achille ; Manetas, Miltos ; Merz, Gerhard ; Messager, Annette ; Nanney, Chuck ; Parsons, Laurie
Spaans & Frans & Engels
This is yesterday / Esto es Ayer, CAAC (Centro Andaluz de Arte Contemporaneo) Sevilla, 16 Febrero - 25 Abril 1999
boek